MANAGEMENT MENINGKATKAN MUTU MADRASAH TSANAWIYAH KESUMA LKMD NAMORAMBE KABUPATEN DELI SERDANG - Uswatun Hasanah; Amiruddin Siahaan; Makmur Syukri (Universitas Indraprasta PGRI, 2023)
This research is to describe how Management Improves the Quality of Madrasah Tsanawiyah Kesuma LKMD Namorambe Deli Serdang Regency The development of madrasah quality is one of the duties and functions of the madrasah head as a leader is one of the determining factors in developing quality in madrasas. The principal of the madrasa as the highest leader in the school, the patterns and strategies in leading have a very large influence on the progress of the madrasa. Control over the use of existing resources in the madrasa by the head of the madrasa is by utilizing the facilities and infrastructure and resources in the madrasa. Collection of research evidensi obtained by observation techniques, interviews and documentation studies. The evidensi analysis step is to collect data, reduce evidensi and then conclude the data. To determine the validity of the data, it is necessary to check the validity of the data, including: credibility, transferability, dependability and confirmability. The results of this study concluded that: 1) Madrasah heads in developing the quality of madrasah required: Madrasah head performance, Adequate madrasah facilities and infrastructure, Increased teacher competence in madrasas, Student extracurricular activities. 2) Control of the madrasah head to develop the quality of the madrasah is needed: Control of education financing, Scheduled and unscheduled controls, Control of facilities and infrastructure. Madrasa quality assurance carried out by madrasa heads in improving the quality of madrasas are: Education report cards, Student Graduate Improvement, Teacher Career Improvement.